2019
DOI: 10.3390/nu12010077
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adherence to the Mediterranean Diet and Physical Fitness with Body Composition Parameters in 1717 European Adolescents: The AdolesHealth Study

Abstract: Obesity, low levels of physical fitness, and unhealthy eating patterns are responsible for part of the health problems of adolescents today. The current study aimed at examining the association between the adherence to the Mediterranean diet (MD), through each answer to the items of the Adherence to the MD Questionnaire (KIDMED), and physical fitness with body composition parameters (body mass index (BMI), percentage of body fat, and waist circumference) in 1717 European adolescents (N = 900 boys, N = 817 girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 89 publications
2
30
0
4
Order By: Relevance
“…As recently evidenced in cross-sectional investigations, adherence to the Mediterranean eating style can give health advantages starting from young age [23]. The consumption of fish, nuts and dairy products, representing a fundamental aspect in the MedDiet, can be related to a better body composition and fitness performance in adolescents, in terms of speed/agility and cardiorespiratory endurance [23]. Nonetheless, even in European countries surrounding the Mediterranean Sea, half of the children and adolescents show only a low adherence to this healthy dietary tradition [24], with a high rate of pediatric overweight and development of obesity and related complications in adult life.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…As recently evidenced in cross-sectional investigations, adherence to the Mediterranean eating style can give health advantages starting from young age [23]. The consumption of fish, nuts and dairy products, representing a fundamental aspect in the MedDiet, can be related to a better body composition and fitness performance in adolescents, in terms of speed/agility and cardiorespiratory endurance [23]. Nonetheless, even in European countries surrounding the Mediterranean Sea, half of the children and adolescents show only a low adherence to this healthy dietary tradition [24], with a high rate of pediatric overweight and development of obesity and related complications in adult life.…”
mentioning
confidence: 88%
“…Phenolic compounds from plant sources may also modulate insulin action and metabolism in insulin-sensitive tissues, with potential preventive or curative effects against IR and IR-related diseases. As recently evidenced in cross-sectional investigations, adherence to the Mediterranean eating style can give health advantages starting from young age [23]. The consumption of fish, nuts and dairy products, representing a fundamental aspect in the MedDiet, can be related to a better body composition and fitness performance in adolescents, in terms of speed/agility and cardiorespiratory endurance [23].…”
mentioning
confidence: 98%
“…For this reason, the relationship between adherence to the MD, PA, sedentary behaviours and different parameters of physical fitness has been analysed in several studies, but inconsistent results have been reported, and a metaanalytic understanding of how the MD adherence contributes to healthy habits and Downloaded from https://www.cambridge.org/core. IP address: 44.224.250.200,on 21 Dec 2020 at 02:52:56, subject to the Cambridge Core terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0007114520004894 physical fitness in youth remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle changes are a critical part of obesity prevention and intervention and are being pursued by public health organizations to promote health [ 5 ]. Physical inactivity and sedentary behavior are two powerful drivers of the obesity pandemic [ 6 ] and have been linked to an increased prevalence of disease and an increased risk of all-cause mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%